Possible interactions between antioxidant enzymes and free sialic acids in saliva: A preliminary study on elite judoists - Cavas, L.; Arpinar, P.; Yurdakoc, K. (International Journal of Sports Medicine, 2005)
Measurement of antioxidant enzyme activities is of great importance in the evaluation of oxidative stress in human metabolism. Sialic acids are also vital bio-markers for some diseases such as acute myocardial infarction and diabetes. In the present study, antioxidant enzyme activities (SOD, CAT, GSH-Px) and free sialic acid (FSA) levels in saliva were determined before and after training in the elite Turkish judoists (ETJ). According to the results, antioxidant enzyme activities in post-exercise values were significantly (p < 0.05) higher than those of pre-exercise values. A major finding of this study was that FSA levels also increased significantly (p < 0.05). Superoxide radical anion might have been effectively dismutated to hydrogen peroxide by elevated SOD activity. Accordingly, it suggests that CAT, having a higher increasing rate, was more efficient than GSH-Px in decomposition of hydrogen peroxide. In conclusion, the increase in antioxidant enzyme activities might have caused the elevation of FSA levels after training. Over-excreted sialic acids to saliva might have an important role in the removal of hydrogen peroxide. Since the increase in FSA levels in saliva has been found to be in well accordance with antioxidant enzymes, FSA may be concluded as an alternative oxidative stress marker in athletes.